Screw compressors : mathematical modelling and performance calculation - Stosic, Nikola, ....-; Kovačević, Ahmed, ....-; Smith, Ian K., 1932- (Berlin : Springer, 2005)
The first part of Screw Compressors gives a review of recent developments in screw compressor design. The second part presents a generalized mathematical definition of screw machine rotors and describes some well known lobe shapes in detail. The third part treats the mathematical modelling of the thermodynamics and fluid mechanics of compression and expansion processes. This includes discussion of the issues addressed in order to be able to predict the optimum rotor size and speed and built-in volume ratio and, in the case of oil flooded machines, the injection position and jet diameter. The fourth and fifth parts discuss the principles used and describe the application of the analytical procedures and rotor profiling techniques, presented in the earlier chapters, to the design of a number of twin screw compressors, currently manufactured including the examples of combining expansion and compression in the same machine.
Includes bibliographical references (p. [133]-138).
Keywords: Screw compressors